Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/ssqu.13134
|View full text |Cite
|
Sign up to set email alerts
|

The impact of parental monitoring on cyberbullying victimization in the COVID‐19 era

Abstract: Objective: The purpose of the current research was to examine the predictors of cyberbullying victimization among South Korean students during a period in which the coronavirus disease was spreading worldwide. We assessed whether parental guardianship protected against victimization when most people worked from home and school instructions were shifted to online learning. Methods: We analyzed nationally representative data collected between October 6 and November 13, 2020. Binary logistic regression models wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 41 publications
(83 reference statements)
1
19
0
Order By: Relevance
“…The digital platforms' use for educational purposes and social interaction amongst adolescents significantly increased during the COVID-19 lockdown (Mkhize & Gopal, 2021). Research evidence suggests that as due to the virtual environment during COVID-19, adolescents prone to bullying behaviour were possibly more likely to cyber bully (Barlett et al, 2016;Paek et al, 2022). The findings of this study show how cyberbystanders react emotionally and behaviourally when they witness cyberbullying during the Covid-19 epidemic.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The digital platforms' use for educational purposes and social interaction amongst adolescents significantly increased during the COVID-19 lockdown (Mkhize & Gopal, 2021). Research evidence suggests that as due to the virtual environment during COVID-19, adolescents prone to bullying behaviour were possibly more likely to cyber bully (Barlett et al, 2016;Paek et al, 2022). The findings of this study show how cyberbystanders react emotionally and behaviourally when they witness cyberbullying during the Covid-19 epidemic.…”
Section: Discussionmentioning
confidence: 67%
“…The shift to a remote form of contact following the outbreak of COVID-19 further necessitated using digital platforms for social and educational purposes (Mkhize & Gopal, 2021). As the use of the internet and information technology for social and educational purposes increase, adolescents prone to bullying behaviour are provided with increased opportunities to perpetrate aggressive behaviour online and also possibly, are more likely to cyberbully (Barlett et al, 2016;Cara, 2022;Paek et al, 2022). Cyberbullying is a devastating type of bullying that has emerged due to technological advancements in the twenty-first century (Singh & Steyn, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with research that has found that about half of teachers were unsure of whether cyberbullying was a school related‐issue and that many teachers report that effective ways to address cyberbullying were through increased parental involvement and greater discipline for cyberbullying (Stauffer et al, 2012). Research during the COVID‐19 pandemic supports this, finding that increased parental supervision of online behaviors, parent‐child interactions, school involvement, and cyberbullying education decreased cyberbullying in youth (Paek et al, 2022; Shin & Choi, 2021). These findings also reflect the NASP Practice Model domain area that emphasizes the importance of strong communities of support and underscore the value of a comprehensive approach that includes parental involvement in addressing cyberbullying issues (Stauffer et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Enduring factors are usually stable over time, including personal characteristics (e.g., demographic factors, socioeconomic status, history of bullying) (Jain et al, 2020;Lee et al, 2022;Shin & Choi, 2021;Trompeter et al, 2022), cultural factors and individual consciousness (e.g., Confucian responsibility thinking, awareness of cyberbullying) (Wang et al, 2022;. Transient factors are fluctuating conditions that may be affected by the pandemic, including cyber factors (e.g., online activities) (Ikeda et al, 2022;Jain et al, 2020;Maftei et al, 2022;Paek et al, 2022), mesosystems (e.g., family support, school engagement) (Rodriguez-Rivas et al, 2022;Shin & Choi, 2021), and virus-related stressors (e.g., COVID-19 infection) (Barlett, Rinker, et al, 2021;Teng et al, 2021). Among the above factors, more internet use, and some personal characteristics such as history of bullying were common risk factors for cyberbullying victimization and perpetration (Lee et al, 2022;Jain et al, 2020;Shin & Choi, 2021;Vejmelka & Matković, 2021).…”
Section: Introductionmentioning
confidence: 99%